Usage of and attitudes about green tea extract and Epigallocathechin-3-gallate (EGCG) as a therapy in individuals with Down syndrome. (August 2019) - Long, Rachel; Drawbaugh, Montana L.; Davis, Charlene M.; Goodlett, Charles R.; Williams, Jane R.; Roper, Randall J.
Highlights: Eighteen percent of caregivers gave green tea extract (GTE) or Epigallocathechin-3-gallate (EGCG) to individuals with DS. Most caregivers who gave GTE or EGCG were younger and highly educated. Most caregivers utilized the internet, scientific publications and other parents to understand about GTE or EGCG. The majority of individuals who received GTE or EGCG were reported as less severely affected. Abstract: Objective: Usage of and views concerning alternative therapies in the DS community are not well documented. Some positive effects of green tea extracts (GTE) containing Epigallocathechin-3-gallate (EGCG) have been reported in individuals with DS and DS mouse models, but minimal improvements or detrimental effects of pure EGCG treatment have been reported in DS mouse models. Given the uncertainty about the effectiveness of these supplements, the goal of this study was to determine the relative prevalence of and attitudes about GTE/EGCG treatments among DS caregivers. Methods: An anonymous survey about attitudes and usage of GTE/EGCG in individuals with DS was completed by caregivers of these individuals. Results: GTE/EGCG treatment was provided by 18% of responding caregivers who were mostly younger, highly educated, and utilized scientific sources and other parents to influence their decision to use GTE/EGCG. Individuals with DS who received GTE/EGCG were characterized as less severely disabled. Most caregivers who did not give GTE/EGCG reported concerns about potential side effects and lack of effectiveness. Few caregivers consulted with medical providers about GTE/EGCG usage. Conclusions: These results demonstrate a need for communication between caregivers, medical providers, and scientists about potential benefits and risks for adverse effects of GTE, EGCG, and other nutritional supplements in individuals with DS.